2020
DOI: 10.1053/j.gastro.2020.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell-Derived Neurotrophic Factor Induces Enteric Neurogenesis and Improves Colon Structure and Function in Mouse Models of Hirschsprung Disease

Abstract: Muscle explants myenteric neural ganglion WT-like neural ganglia, colon function and microbiota inflammed submucosa disrupted epithelial barrier thicker muscles dysbiosis Untreated Hirschsprung mouse GDNF-treated Hirschsprung mouse Wild type mouse P20 distal colon no enteric nervous system, megacolon, premature death Mouse models of Hirschsprung disease exogenous GDNF P20/P56 enema P4 P8 P0 e n d o g e n o u s G D N F hypertrophic extrinsic nerve with Schwann cells submucosal neural ganglion People with Hirsch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 52 publications
5
69
0
Order By: Relevance
“…Regenerative medicine and trophic factor modulation hold promise for treating life-threatening enteric neuropathies. 2 , 3 To facilitate reprogramming and improve bowel function, better understanding of the molecular identity and characteristics of ENS subtypes is needed. 2 We used single-cell transcriptomics to identify hundreds of neurotransmitters, receptors, ion channels, signaling molecules, and messenger RNA regulatory genes differentially expressed in 7 mouse myenteric neuron subclasses in adult distal colon and 8 neuron groups at E17.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regenerative medicine and trophic factor modulation hold promise for treating life-threatening enteric neuropathies. 2 , 3 To facilitate reprogramming and improve bowel function, better understanding of the molecular identity and characteristics of ENS subtypes is needed. 2 We used single-cell transcriptomics to identify hundreds of neurotransmitters, receptors, ion channels, signaling molecules, and messenger RNA regulatory genes differentially expressed in 7 mouse myenteric neuron subclasses in adult distal colon and 8 neuron groups at E17.5.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we have limited ability to identify missing or defective ENS cell populations in people with bowel dysmotility, and therapies are inadequate. Promising new approaches like regenerative medicine 2 or glial cell line–derived neurotrophic factor (GDNF)–induced regeneration of the ENS 3 would benefit from a more thorough characterization of the transcription factors, receptors, and signaling pathways that define enteric neuron subclasses.…”
mentioning
confidence: 99%
“…Similarly, we demonstrated increased NCC survival and growth in a chemically induced HSCR rat model, by using a ROCK inhibitor (Zhao et al, 2020). Another study found that administration of glial cell derived neurotrophic factor (GDNF) rescued megacolon, prevented death and stimulated ENS regeneration in the Holstein (a model for trisomy 21associated HSCR), TashT (a model for male-biased HSCR) and Piebald-lethal (a model for EDNRB mutation-associated HSCR) mice models (Soret et al, 2020). These results suggest that factors expressed by cells other than enteric neurons, are able to promote proliferation and engraftment of ENCCs.…”
Section: Identification Of Drugs That Stimulate Ens Developmentmentioning
confidence: 96%
“…2F), ruling out the possibility that our vDAO preparation might have contained another substance with anti-histamine activity. Moreover, the muscle relaxing activity of vDAO seems to be specific for histamine-induced contractions as vDAO had no impact on L-NAME-provoked 43 muscle contractions ( Fig. S1).…”
Section: Resultsmentioning
confidence: 98%